2016
DOI: 10.1097/cmr.0000000000000262
|View full text |Cite
|
Sign up to set email alerts
|

Investigating associations of cyclooxygenase-2 expression with angiogenesis, proliferation, macrophage and T-lymphocyte infiltration in canine melanocytic tumours

Abstract: Cyclooxygenase-2 (COX-2) is known to be involved in tumour progression and has been suggested as a therapeutic target in many human and animal malignancies. A number of different pathways subjacent to cancer hallmarks are considered to be involved in COX-2-mediated tumour progression, although these are still largely undefined. Our aim is to investigate associations between COX-2 expression and angiogenesis, proliferation and the inflammatory microenvironment in canine melanocytic tumours. Understanding the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 54 publications
3
17
0
Order By: Relevance
“…The positivity for S-100, Melan-A, PNL-2 26 and COX-2 27 was indicated by the presence of distinct brown cytoplasmic labelling and it was used a semiquantitative method previously described. 13,23 The number of COX-2 positive cells was evaluated semi-quantitatively, with the distribution score defined by the estimated percentage of positive cells in five fields at ×400 magnification: 0 = absence, 1 = fewer than 10% stained cells, 2 = between 10% and 30%, 3 = between 31% and 60%, 4 = more than 61% stained cells. For staining intensity, values from 0 to 3 were attributed: 0 = absence (−), 1 = weak staining (+), 2 = moderate staining (++), and 3 = strong staining (+++).…”
Section: Quantification Of Immunoreactivitymentioning
confidence: 99%
See 2 more Smart Citations
“…The positivity for S-100, Melan-A, PNL-2 26 and COX-2 27 was indicated by the presence of distinct brown cytoplasmic labelling and it was used a semiquantitative method previously described. 13,23 The number of COX-2 positive cells was evaluated semi-quantitatively, with the distribution score defined by the estimated percentage of positive cells in five fields at ×400 magnification: 0 = absence, 1 = fewer than 10% stained cells, 2 = between 10% and 30%, 3 = between 31% and 60%, 4 = more than 61% stained cells. For staining intensity, values from 0 to 3 were attributed: 0 = absence (−), 1 = weak staining (+), 2 = moderate staining (++), and 3 = strong staining (+++).…”
Section: Quantification Of Immunoreactivitymentioning
confidence: 99%
“…22 A study that evaluated the COX-2 expression with angiogenesis, tumour proliferation, presence of macrophages and T-lymphocyte infiltrate in canine melanomas found associations with microvessel density (MVD) (FACTOR VIII), lymphocyte infiltration and macrophages. 23 However, the association between COX-2 expression and molecular markers of inflammatory infiltrate, angiogenesis and proliferation are not well described in either human or canine. Building on previous reports of canine melanomas and COX-2 expression.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have evaluated macrophage infiltrates in canine melanoma, mammary carcinoma, seminoma, glioma and nasal carcinoma . In canine mammary tumours, an association between a high density of tumour‐associated macrophages (TAMs) and significantly decreased overall survival times was reported .…”
Section: Introductionmentioning
confidence: 99%
“…Osteopontin combined with PGE2 substantially increases the influence on angiogenesis by enhancing the expression of MMP-9 (36). Another study revealed that the increased expression of COX-2 in melanoma tumor types is associated with increased VEGF expression, density of micro vessels and inflammatory infiltration formed of macrophages (37,38).…”
Section: Macrophages In Skin Melanomasmentioning
confidence: 99%